USER ACCEPTANCE OF MOBILE-JKN: INSIGHTS FROM THE TECHNOLOGY ACCEPTANCE MODEL - Ferina Septiani Damanik; Anna Wahyuni Widayanti; Chairun Wiedyaningsih (Jurnal Administrasi Kesehatan Indonesia)
Background: Technological advancements in healthcare have driven BPJS Kesehatan Indonesia to develop the Mobile JKN application to enhance accessibility, efficiency, and quality of services. Despite its potential benefits, the implementation of this application faces various challenges, such as application errors, differing levels of digital literacy, and data security issues, necessitating an evaluation of its adoption and acceptance.